Reassessing cellular glutathione homoeostasis: novel insights revealed by genetically encoded redox probes - Morgan, Bruce (Biochemical Society transactions, 2014)
Glutathione is the most abundant small molecule thiol in nearly all eukaryotes. Whole-cell levels of oxidized (GSSG) and reduced (GSH) glutathione are variable and responsive to genetic and chemical manipulations, which has led to their relative levels being widely used as a marker of the 'cellular redox state' and to indicate the level of 'oxidative stress' experienced by cells, tissues and organisms. However, the applicability of glutathione as a marker for a generalized 'cellular redox state' is questionable, especially in the light of recent observations in yeast cells. In yeast, whole-cell GSSG changes are almost completely dependent upon the activity of an ABC-C (ATP-binding cassette-C) transporter, Ycf1 (yeast cadmium factor 1), which mediates sequestration of GSSG to the vacuole. In the absence of Ycf1 whole-cell GSSG content is strongly decreased and extremely robust to perturbation. These observations are consistent with highly specific redox-sensitive GFP probe-based measurements of the cytosolic glutathione pool and indicate that cytosolic GSSG reductive systems are easily able to reduce nearly all GSSG formed, even following treatment with large concentrations of oxidant. In the present paper, I discuss the consequences of these new findings for our understanding of glutathione homoeostasis in the eukaryotic cell.
Gesehen am 08.12.2020